1996
DOI: 10.1524/ract.1996.74.special-issue.271
|View full text |Cite
|
Sign up to set email alerts
|

Clays at the Natural Nuclear Reactor at Bangombé, Gabon: Migration of Actinides

Abstract: Clay minerals were examined from the natural nuclear reactor at Bangombé. The clay mineralogy of the reactor facies is: illite, kaolinite and minor chlorite (FB formation) ; illite with chlorite and kaolinite in hydrothermal veins (argile de pile) ; illite and chlorite (reactor core); and i) chlorite and kaolinite ± illite ± smectite or ii) illite in the underlying FA formation. Illite crystallinity values are in general highest in rocks that experienced the highest temperatures during reactor operation. Chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Eberly et al (1995) noted a close spatial relationship between uraninite and Fe-bearing chlorite in hydrothermal veins associated with the natural nuclear reactor at Bangombe, Republic of Gabon. Based on the textural relationship between uraninite and chlorite, Eberly et al (1996) suggested that chlorite heterogeneously reduced aqueous uranyl to U IV in uraninite. Wersin et al (1994) and Liger et al (1999) demonstrated that pyrite and Fe II adsorbed to ␣-Fe 2 O 3 can heterogeneously reduce U VI to U IV .…”
Section: Introductionmentioning
confidence: 99%
“…Eberly et al (1995) noted a close spatial relationship between uraninite and Fe-bearing chlorite in hydrothermal veins associated with the natural nuclear reactor at Bangombe, Republic of Gabon. Based on the textural relationship between uraninite and chlorite, Eberly et al (1996) suggested that chlorite heterogeneously reduced aqueous uranyl to U IV in uraninite. Wersin et al (1994) and Liger et al (1999) demonstrated that pyrite and Fe II adsorbed to ␣-Fe 2 O 3 can heterogeneously reduce U VI to U IV .…”
Section: Introductionmentioning
confidence: 99%
“…Along with U, chlorite has also the potential to sorb Pu. This was demonstrated by an experiment in which thin sections from the Bangomb6 deposit remained in contact with a solution containing 10-6M 239pu (Eberly et al 1996). After exposure, the distribution of Pu by autoradiography indicated that adsorption of Pu was much more effective onto chlorite than illite and kaolinite.…”
Section: Mechanisms Of U Retention At Cigar Lakementioning
confidence: 98%
“…4). Studies of the clay halo at the Oklo and Bangomb~ natural reactors have shown that chlorites are efficient actinide scavengers (Bros et al 1993;Eberly et al 1995Eberly et al , 1996GauthierLafaye et al 1996; and revealed the sorption of significant amounts of U (100-1000ppm) onto Fe-Mg chlorite . Along with U, chlorite has also the potential to sorb Pu.…”
Section: Mechanisms Of U Retention At Cigar Lakementioning
confidence: 99%
“…It has also been shown that certain clay minerals have an affinity for actinides (Eberly 1996). found in K basin sludges, and because the KE basin concrete walls were produced from local aggregates, and because soil and sand have blown into the basins over the years, we cannot rule out these possibilities as being present in general sludges, and perhaps a portion of them might survive the acid-dissolution to become part of the residue.…”
Section: Actinide-absorbing Mineral Smentioning
confidence: 99%